A systematic review on heart rate variability in Bulimia Nervosa - Peschel, Stephanie; Feeling, Nicole R.; Vögele, Claus; Kaess, Michael; Thayer, Julian F.; Koenig, Julian (Neuroscience & biobehavioral reviews, 2016)
Eating disorders are associated with alterations of the autonomic nervous system (ANS). Among other indices, heart rate variability (HRV) provides a readily available index of ANS function. While ANS dysfunction indexed by HRV in Anorexia Nervosa has been addressed in previous reviews, here we aimed to review the current evidence on HRV in Bulimia Nervosa (BN). A systematic literature search in Web of Science, PsycInfo, Scopus, and PubMed identified 17 studies reporting HRV in patients with BN. Studies described (i) differences in resting state HRV in patients compared to controls, (ii) alterations in the stress response in BN indexed by HRV, and (iii) treatment effects on HRV in patients with BN. Despite a number of conflicting results, we conclude that BN is characterized by increased resting state vagally-mediated HRV and an impaired stress-response. Intervention-studies suggest that altered ANS-activity in BN is at least partially reversible. Future studies on the complex relation between BN and HRV should investigate the effect of comorbid disorders, subtypes of BN, and mechanisms affecting treatment outcome.
Available online 30 January 2016
Gesehen am 08.10.2020